Effects of zein modifying polar amino acids as surface stabilizers on the emulsification stability of milk cream diacylglycerol. (1st August 2022) - Xue, Xiuheng; He, Haiyong; Liu, Cunjun; Han, Yanping; He, Jingrui; Zhou, Jiajia; Guo, Xinglei; Wang, Juhua; Cheng, Jianbo
Abstract: It is important to improve the emulsification stability of oil-in-water emulsions by surface loading hydrophilic groups. l -Glutamic acid (Glu), l -Glutamine (Gln) and l -Arginine (Arg) were used to modify Zein-Chitosan lactate (CHL) as stabilizers to improve the emulsification stability of milk cream diacylglycerol (DAG). The mechanism of using polar amino acids to enhance the emulsification of DAG-in-water emulsion was explored. The results showed that the average droplet size of DAG emulsion was 48 μm by using Zein-CHL-Gln as surface stabilizer when the pH was 6.0, and the ratio of Gln and CHL was 1:1. Zein-CHL-Gln as surface stabilizer could improve the emulsion index by 25% compared with the control group after storage for 7 days. Hydrophobic interaction between L-Gln and zein played an important role in increasing the hydrophilic polar moiety on the emulsion surface. Zein-CHL modified with l -Glutamine was better surface stabilizer to improve the emulsification of oil-in-water emulsions. Highlights: Zein modified with polar amino acid can improve the surface hydrophilicity of oil-in-water emulsion. Zein-CHL modified with l -Glutamine was better to be used as stabilizer of oil-in-water emulsion. Zein-CHL modified with l -Glutamine can improve the emulsification of diacylglycerol in water phase.